Couple-kissing flaps for successful repair of severe sacral pressure ulcers in frail elderly patients - Jing-Chun Zhao; Bo-Ru Zhang; Kai Shi; Jia-Ao Yu; Jian Wang; Qing-Hua Yu; Lei Hong (BMC Geriatrics, 2017)
Abstract Background Surgical repair of severe pressure ulcers (PUs) in elderly patients remains a challenge for clinicians due to the complicated comorbidities and the special physical characteristics of elderly patients. The objective of this study was to evaluate the application of couple-kissing flaps (CKF) in the reconstruction of sacral PUs in these patients. Methods Elderly patients (over 70 years) with stage 3 or stage 4 PUs who underwent CKF immediately after radical debridement between July 2012 and December 2015 were enrolled in this retrospective study. Patients’ demographics were extracted from the medical records. Results A total of 12 patients were involved in this study. The average age of the patients was 76.83 years (ranged from 71 to 92 years). The donor site was closed primarily in all cases. All the flaps healed uneventfully without complications. Follow-up observations were conducted for an average of 13.6 months (ranged from 9 months to 2 years). Cosmetic results were satisfactory, with no surgical site breakdown or recurrence of PU in any of the cases. Three representative cases are presented. Conclusions The CKF is a reliable and satisfactory option for the reconstruction of severe sacral PUs defects in elderly patients. CKF is associated with an relatively low rate of complications and recurrence.